The urban sanitation conundrum: what can community-managed programmes in India unravel?. (October 2015) - Das, Priyam
The urban landscape in India is dotted with water and sanitation projects centred on the mantra of community participation and management. Yet there is much that remains to be learned about such projects, particularly in smaller urban centres where the pressures of urbanization are threatening to overwhelm local government efforts to provide basic services. Drawing on case studies of community-managed sewerage programmes in two cities in central India, this paper explores the status of sanitation in low-income, informal settlements and critically examines how such programmes unfold on the ground. The findings highlight lessons for future sanitation policy and programmes.